Axial compressive behavior of mega steel-reinforced high-strength concrete columns with different steel sections. (February 2023) - Dong, Hongying; Zhu, Jian; Cao, Wanlin; Rao, Yixuan
Abstract: Steel-reinforced concrete columns are the crucial vertical load-bearing members in the frame composite structures. Previous studies on steel-reinforced concrete columns primarily focus on simple H-shaped and cruciform steel sections; insufficient attention is paid to mega columns, which are frequently designed with complex steel sections and high-strength concrete. In this study, four scaled mega columns, including two open-shaped and two multicell-shaped steel-reinforced high-strength concrete columns with cross-sectional dimensions of 700 × 700 mm and different concrete strengths, were subjected to one-way repeated compression tests. The aforementioned tests were conducted to examine the damage evolution, load-axial deformation response, bearing capacity, strain development, stiffness degradation, ductility, and restoration capacity of the columns. The test results indicate that the multicell steel section effectively alleviates crack widening and concrete spalling, and improves the post-peak stiffness and ductility. With increasing concrete strength, the peak load, initial stiffness, and restoration capacity are improved, while the ductility is impaired, and more abrupt damage is recorded. Three existing codes were examined to calculate the bearing capacity with a conservative estimation, particularly the ACI 318-11, with a mean predicted result to test result ratio of 0.76. Hence, an analytical model considering the confinement provided by stirrups and steel sections was proposed to predict the load-axial displacement curve with desirable accuracy. Furthermore, a finite element model based on the division of different confined concrete was established to further explore the damage evolution and to conduct a parametric study.